Integrating Deep Learning and Contextual Learning Teaching: Fostering Motivation and Sustainability in Bilingual Education - Dzulkurnain, Mohammad Iskandar; Lasaten, Ronald Candy S; Fitriyana, Laili Nur (Universitas PGRI Yogyakarta, 2026)
Student motivation remains a persistent challenge in 21st-century education, particularly in bilingual classroom contexts where linguistic diversity and instructional relevance intersect. While previous studies have examined deep learning approaches and contextual learning strategies separately, limited attention has been given to their integrated application in addressing motivational challenges within authentic classroom settings. Responding to this gap, this qualitative case study explores how the integration of Deep Learning and Contextual Learning Teaching (CLT) enhances student motivation and engagement in a bilingual elementary classroom in Indonesia. Data were generated through systematic classroom observations and supported by a literature-informed analytical framework. The findings indicate that combining conceptual depth with contextualized learning tasks fosters active participation, intrinsic motivation, and reflective learning practices. Students demonstrated increased curiosity, collaborative interaction, and ownership of learning when instructional activities emphasized understanding, application, and reflection within meaningful real-life contexts. This study contributes to ELT pedagogy by illustrating how integrative instructional design can support sustainable and inclusive learning environments in bilingual education. Keywords: Deep Learning, Contextual Learning Teaching, Student Motivation, Bilingual Classroom, Sustainable Education